(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article investigates the cognitive and cultural mechanisms underlying the nomination process of hydronyms in the Uzbek language. Viewing toponymic nomination as a complex interaction between the naming subject (human) and the named object (water body), the study traces the historical evolution of Uzbek hydronyms from generic geographical appellatives to specific proper nouns. The findings demonstrate that the development of agricultural and irrigation culture in Central Asia served as the primary catalyst for hydronymic specification. Using a structural-semantic framework, the research analyzes how physical attributes, anthropocentric factors, and local flora/fauna operate as core naming motivations. The study concludes that hydronyms are not arbitrary labels but crystallizations of centuries of human empirical experience and environmental interaction.